2010
DOI: 10.4097/kjae.2010.59.4.265
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the neuroendocrine and inflammatory responses after laparoscopic and abdominal hysterectomy

Abstract: BackgroundLaparoscopic surgery is associated with a more favorable clinical outcome than that of conventional open surgery. This might be related to the magnitude of the tissue trauma. The aim of the present study was to examine the differences of the neuroendocrine and inflammatory responses between the two surgical techniques.MethodsTwenty-four patients with no major medical disease were randomly assigned to undergo laparoscopic (n = 13) or abdominal hysterectomy (n = 11). Venous blood samples were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 20 publications
0
22
0
2
Order By: Relevance
“…4 This has also been seen with laparoscopic hysterectomy where a recent study showed a decrease in circulating interleukin (IL)-6 and Creactive protein (CRP) compared with open hysterectomy. 5 The severity of the inflammatory response to a standardized surgical insult has been shown to be widely variable, with human studies using a cardiopulmonary bypass model attributing such variability to genetic polymorphism. 6 Patients with higher pro-inflammatory responses were shown to be prone to a greater incidence of postoperative complications.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…4 This has also been seen with laparoscopic hysterectomy where a recent study showed a decrease in circulating interleukin (IL)-6 and Creactive protein (CRP) compared with open hysterectomy. 5 The severity of the inflammatory response to a standardized surgical insult has been shown to be widely variable, with human studies using a cardiopulmonary bypass model attributing such variability to genetic polymorphism. 6 Patients with higher pro-inflammatory responses were shown to be prone to a greater incidence of postoperative complications.…”
Section: Résumémentioning
confidence: 99%
“…The fact that the overall inflammatory response during laparoscopy is significantly attenuated may indicate an overall lesser degree of tissue damage. 4,5 This would explain, at least in part, the improved postoperative functional state following laparoscopy compared with conventional laparotomy. Thus, minimally invasive surgery remains an essential component of any ERAS program.…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
“…Some studies have shown that laparoscopic surgery may lead to a decreased hormonal stress response in patients, which may result in decreased complication rates, morbidity and mortality [7,8]. The evidence has, however, not been conclusive and many studies in other fields of surgery show no statistically significant difference [5,9,10]. It has been suggested that the effect might be different in major surgery and this has been pointed out as an area for further research [5].…”
Section: Introductionmentioning
confidence: 99%
“…They suggest that both vaginal or laparoscopic approach have superior results than abdominal hysterectomy [6][7][8][9] . One possible evolution of laparoscopy, i.e., singleport access, aims to further reduce the surgical morbidity and is associated with better cosmetic results 10,11 .…”
Section: ■ Introductionmentioning
confidence: 99%